Factibilidad Para La Creación De Una Empresa Industrializadora De Café Órganico En La Ciudad De Loja - Abad Villalta, Diana Isabel (2016)
This project aims to establish a market research, technical, financial and evaluation thereof, aimed at demonstrating the feasibility of creating a producer and marketer of organic coffee in the city of Loja, originating enterprise based to the various problems of the society, such as lack of employment that leads many people to seek ways to engage in their own businesses, with new ideas that contribute to the improvement and growth of the same. For all of the above is necessary to provide different ideas that contribute to the growth of new businesses such as the company's production and marketing of organic coffee that meets the same satisfying various tastes and preferences of consumers of this drink as traditional for decades has remained. For this applies a methodology based on the various research methods and the scientific, deductive and inductive that allowed the execution. Speaking of this market research project concludes that the research population were the families of the urban area of the city of Loja, obtaining a population of 24.050, proceeding to match supply to demand, since there were no relevant data and current thereof. This study proceeds to identify potential applicants and the real and effective with those who were unable to determine what the average daily consumption of organic coffee for families Lojanas, which in this case is 0.44 kg of coffee equivalent to two tablespoons per family. In the preferences for hot drinks, consumers have different trends, which is why we present several complementary products and coffee substitutes. This project will have a useful life of five years and its processing plant will locate in the neighborhood "The Brambles 2" this being a location away from the city center, which will not cause nuisance to neighboring families of same, it is noteworthy that the installed capacity of 21.120 kg of coffee per year, determining a capacity used for the first year of 17.952 kg of coffee, considering that in the following years the production will be incremental. Also with regard to the organization of the company, will be made up of a limited liability company and will consist of a manager, legal adviser, secretary - accountant, and staff necessary for the production process of organic coffee. We conclude that the project is feasible by the results of economic and financial calculations, they are updated with the various tax obligations, labor and employers who must comply with current government policies and regulations, with an initial investment of $ 31.732,52 plus the evaluation obtained a positive VAN of $ 30.677,91 cost benefit ratio of 1.10, the TIR is 35,56% and a sensitivity of 1.16 % In cost increases 2.30% In decline in revenue.